Mitochondria-targeted curcumin loaded CTPP–PEG–PCL self-assembled micelles for improving liver fibrosis therapy. Issue 10 (28th January 2021) - Zhang, Liqiao; Pan, Xiuhua; Xu, Lixing; Zhang, Linlin; Huang, Haiqin
Abstract : A mitochondria-targeting micelle system based on CTPP–PEG–PCL polymer was designed to deliver curcumin to active HSC-T6 cells and prolong the systemic circulation and bioavailability of curcumin in vivo for effective treatment of liver fibrosis. Abstract : Liver fibrosis, originating from activated hepatic stellate cells (HSCs), is receiving much attention in the treatment of clinical liver disease. In this study, mitochondria-targeted curcumin (Cur) loaded 3-carboxypropyl-triphenylphosphonium bromide–poly(ethylene glycol)–poly(ε-caprolactone) (CTPP–PEG–PCL) micelles were constructed to prolong the systemic circulation of Cur, improve the bioavailability of Cur and play a precise role in anti-fibrosis. The prepared Cur–CTPP–PEG–PCL micelles with a spherical shape had satisfactory dispersion, low critical micelle concentration (CMC) and high encapsulation efficiency (92.88%). The CTPP modification endowed good endosomal escape ability to the CTPP–PEG–PCL micelles, and micelles could be selectively accumulated in mitochondria, thereby inducing the enhanced cell proliferation inhibition of HSC-T6 cells. Mitochondrial Membrane Potential (MMP) was greatly reduced due to the mitochondrial-targeting of Cur. Moreover, the system circulation of Cur was extended and bioavailability was significantly enhanced in vivo . As expected, Cur loaded CTPP–PEG–PCL micelles were more effective in improving liver fibrosis compared with Cur and Cur–mPEG–PCL micelles. In conclusion, the Cur–CTPP–PEG–PCL based micelles can be a potential candidate for liver fibrosis treatment in future clinical applications.